Hardiness Pada Ibu Bekerja - Indah Antika Putri, Yayan, Rini Lestari, S.Psi, M.Si (2017)
Hardiness in working mother is a personality characteristics that have durability for the event that can make stress for them. The purpose of this research was to understand and describe the personality of hardiness on working mothers. Subject in this research were housewives who work 8 hours a day outside the home, and have a childern aged 0 until 15 years old This research use qualitative approach. To collect data in this research is using interview and the analysis is using content analysis. The results of the study reveal that the mother who works has a personality of hardiness that is characterized by its commitment to undergo a double role to keep working in the middle of his duties as housewives, can control the unexpected situations such as the role to be performed simultaneously and fatigue, as well as to consider changes happened is normal, not a threatening thing.Working mom never give up in one situation, but they want to make a proggres. Factor that influence hardiness personality in working mom are status of the job, children academic motivation, career motivation and enjoying their job